Biodegradable Microcapsules Loaded with Nerve Growth Factor Enable Neurite Guidance and Synapse Formation - Olga Kopach; Anton M. Pavlov; Olga A. Sindeeva; Gleb B. Sukhorukov; Dmitri A. Rusakov (MDPI AG, 2020)
Neurological disorders and traumas often involve loss of specific neuronal connections, which would require intervention with high spatial precision. We have previously demonstrated the biocompatibility and therapeutic potential of the layer-by-layer (LbL)-fabricated microcapsules aimed at the localized delivery of specific channel blockers to peripheral nerves. Here, we explore the potential of LbL-microcapsules to enable site-specific, directional action of neurotrophins to stimulate neuronal morphogenesis and synaptic circuit formation. We find that nanoengineered biodegradable microcapsules loaded with nerve growth factor (NGF) can guide the morphological development of hippocampal neurons in vitro. The presence of NGF-loaded microcapsules or their clusters increases the neurite outgrowth rate while boosting neurite branching. Microcapsule clusters appear to guide the trajectory of developing individual axons leading to the formation of functional synapses. Our observations highlight the potential of NGF-loaded, biodegradable LbL-microcapsules to help guide axonal development and possibly circuit regeneration in neuropathology.